x(y-z)^2-a(z-y)^3 Factorize this term
Answers
Answered by
8
Answer:
Solution(a) x(1 - b) - y(1 - b) =(1-b)(x-y)
(b) 9r(z + 1) + 3r(z+ 1)=(z+1)(9r+3r)=12r(z+1)
(c) p2+ q2+ 5a(p2+ q2)=1(p2+ q2) + 5a(p2+ q2)=(1+5a)(p2+ q2)
(d) x² + x y + 8x + 8y=x(x+y) + 8(x+y)=(x+8)(x+y)
(e) 3(x + y) - 9(x + y)2=3(x+y)[1-3(x+y)]=3(x+y)(1-3x-3y)
(f) l(3m – 7n) - n(3m – 7n)=(l-n)(3m-7n)
(g) (2m – 5) (3a - 2b) - (2m – 5) (2b – 3a)=(2m-5)[3a-2b -(2b-3a)]=6(2m-5)a
(h) x(1 + y) + (7 + 7y)=(x+7)(1+y)
(i) (6xy + 3x) + (2y + 1)=(3x+1)(2y+1)
(j) x(y – z)2 – a(z - y)3=(y-z)2[x-a(z-y)]=(y-z)2(x-az+ay)
(k) z – 7 + 7 x y – x y z=1( z-7) -xy(z-7)=(1-xy)(z-7)
Step-by-step explanation:
please follow kardo
Answered by
9
Answer:
PLEASE MARK MY ANSWER AS BRAINLIEST !
Step-by-step explanation:
Similar questions